Integrin beta8 (ITGB8) activates VAV-RAC1 signaling via FAK in the acquisition of endometrial epithelial cell receptivity for blastocyst implantation - Vijay Kumar (Nature Portfolio, 2017)
Abstract Integrin beta8 (ITGB8) is involved in the endometrial receptivity. The blastocyst first interacts with the luminal endometrial epithelial cells during its implantation; therefore, we have investigated the signaling of ITGB8 via FAK and VAV-RAC1 in the endometrial epithelial cells. Integrin beta8 was found elevated in epithelial cells at late-pre-receptive (day4, 1600 h) and receptive (day5, 0500 h) stages of endometrial receptivity period in the mouse. Integrins downstream molecule FAK has demonstrated an increased expression and phosphorylation (Y397) in the endometrium as well as in the isolated endometrial epithelial cells during receptive and post-receptive stages. Integrin beta8 can functionally interact with FAK, VAV and RAC1 as the levels of phosphorylated-FAK, and VAV along with the RAC-GTP form was reduced after ITGB8 knockdown in the endometrial epithelial cells and uterus. Further, VAV and RAC1 were seen poorly active in the absence of FAK activity, suggesting a crosstalk of ITGB8 and FAK for VAV and RAC1 activation in the endometrial epithelial cells. Silencing of ITGB8 expression and inhibition of FAK activity in the Ishikawa cells rendered poor attachment of JAr spheroids. In conclusion, ITGB8 activates VAV-RAC1 signaling axis via FAK to facilitate the endometrial epithelial cell receptivity for the attachment of blastocyst.